Phonetic manifestations of cognitive and physical stress in trained and untrained police officers - Jessen, Marianne (International Journal of Speech, Language and the Law, 1997)
Two groups of subjects, one with stress management training and one without, were exposed to two types of psychological stress, one with a dominance in cognitive activity (including memorizing events), one with a dominance in physical activity (including precision shooting) and concentration. Speech samples were recorded in two stress conditions and in two non-stress conditions. Measurements were made of the parameters F0-mean, F0-standard deviation, and syllable duration. Means and standard deviations of F0 were determined both on the intra-syllable and on the utterance level. It was found that F0-mean and intra-syllable F0 standard deviation were most important as indices of psychological stress. Higher values for these parameters were obtained in stressed than in unstressed speech and higher values under physical than under cognitive stress. Experience in stress management training leads to an overall reduction of the verbal stress response, in particular in the cognitive condition.